Surface passivation of nanoporous TiO2 via atomic layer deposition of ZrO2 for solid-state dye-sensitized solar cell applications - Li, Tina C. (2009)
We report here the utilization of atomic layer deposition to passivate surface trap states in mesoporous TiO2 nanoparticles for solid-state dye-sensitized solar cells based on 2,2',7,7'-tetrak.is(N, N-di-p- methoxyphenylamine)9,9'-spirobifluorene (spiro-OMeTAD). By depositing ZrO 2 films with angstrom-level precision, coating the inesoporous TiO2 produces over a two-fold enhancement in short-circuit current density, as compared to a control device. Impedance spectroscopy measurements provide evidence that the ZrO2 coating reduces recombination losses at the TiO2/spiro-OMeTAD interface and passivates localized surface states. Lowfrequency negative capacitances, frequently observed in nanocomposite solar cells, have been associated with the surface-state mediated charge transfer from TiO2 to the spiro-OMeTAD. © 2009 American Chemical Society.